ChatGPT and Kahoot Quizzes for Enhancing Student Engagement in Ethics Education (Contrarius Series: Law & Social Justice, 2026)
In an increasingly digitalised higher education landscape, pedagogical innovation is essential to sustain student engagement and learning effectiveness. This study examines the integration of generative artificial intelligence, specifically ChatGPT, into the teaching of a core university course, Ethics and Civilization (MPU3132), through interactive quizzes conducted via the Kahoot platform. The study explores how ChatGPT-supported quiz activities enhance student engagement, interaction, and higher-order thinking in ethics-related learning contexts. Findings indicate that the incorporation of ChatGPT significantly improves student participation, conceptual understanding of ethical and civilisational issues, and knowledge retention. The use of gamified quizzes further fosters intrinsic motivation and healthy competition, contributing to an active and student-centred learning environment. Importantly, this study contributes to the growing body of literature on AI-assisted pedagogy by demonstrating how generative AI can be meaningfully embedded within formative assessment practices to support sustainable education. The proposed approach offers a scalable and adaptable instructional model for ethics and humanities courses, aligning with global educational sustainability goals and the evolving demands of digital learning ecosystems.